In Vitro Study on Anti-Hepatitis C Virus Activity of Spatholobus suberectus Dunn - Shao-Ru Chen (Molecules, 2016)
Hepatitis C virus (HCV) infects 200 million people worldwide, and 75% of HCV cases progress into chronic infections, which consequently cause cirrhosis and hepatocellular carcinoma. HCV infection is treated with currently considered standard drugs, including direct anti-viral agents (DAAs), alone or in combination with peginterferon-α plus ribavirin. However, sustained viral responses vary in different cohorts, and high costs limit the broad use of DAAs. In this study, the ethanol and water extracts of 12 herbs from Lingnan in China were examined in terms of their inhibitory effect on HCV replication. Among the examined extracts, Spatholobus suberectus ethanol extracts suppressed HCV replication. By comparison, Extracts from Fructus lycii, Radix astragali (root), Rubus chingii Hu (fruit), Flos chrysanthemi Indici (flower), Cassia obtusifolia (seed), Lonicera japonica Thunb (flower), Forsythia suspense Thunb (fruit), Poria cocos (sclerotia), Carthamus tinctorius L. (flower), Crataegus pinnatifida Bge. (fruit), and Leonurus japonicas Houtt. (leaf) extracts failed to show a similar activity. Active S. suberectus fractions containing tannins as the major component also inhibited the in vitro translation of HCV RNA. The combination treatments of single compounds, such as epigallocatechin gallate and epicatechin gallate, were not as potent as crude S. suberectus fractions; therefore, crude S. suberectus extract may be a potential alternative treatment against HCV either alone or in combination with other agents.